EVOLUTION OF THE BASEMENT STRUCTURAL STYLE OF THE NORTH ATLANTIC FROM THE BREAKUP OF THE CONTINENT TO MODERN RIFTING ACCORDING TO THE ANOMALOUS GRAVITY FIELD - Sokolov, S.Yu; Bogoliubskii, V.A. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2025)
The Newfoundland-Iberian segment of the Atlantic-Arctic rift system, bounded by demarcation faults of the 1st order, within which the demarcation boundary of the 2nd order is distinguished, has fundamental differences in the structure of the basement to the north and south of it according to relief and gravity anomalies. Morphometric attribute, that plausibly reflects the basement structures beneath the sedimentary cover around the continental margins and in the region of the Mid-Atlantic Ridge, free of sediments, is the attribute «azimuth», calculated from gravity anomalies in the free air. Evaluation of methods for calculating the quantitative characteristics of this attribute in test areas with a predominance of typical mutually orthogonal structural bottom elements showed that the 2-dimensional spectra of the analyzed field in the local areas, in addition to the orientation of the structures, also show their amplitude in the initial field and their spatial periodicity, and adequately describe the structural style of the basement in modern coordinates, varying from the periphery of the basin to the mid-oceanic ridge. In the process of evolution, the basement with a variable geometry is formed, in which there is rotation in the sea floor plane by ~10–15 ° and deviations due to superimposed atypical structures.